Banking Health Indicators and Their Impact on Credit Risk in the Indonesian Banking Sector - Kelvin Pratama; Akmal Sulistomo; Henny Setyo Lestari; Farah Margaretha (Universitas KH. Abdul Chalim Mojokerto, 2025)
Credit risk is inherent in the banking sector, as banks extend credit to the public as a primary source of income. Banks supervised by the Financial Services Authority (Otoritas Jasa Keuangan, OJK) are required to prioritize prudential principles, leading the OJK to monitor risk management in banking through the Non-Performing Loan (NPL) ratio. Various factors can contribute to an increase in credit risk for banks. This study aims to analyze banking-related factors and macroeconomic factors that may influence credit risk. The independent variables related to banking include SIZE, ROA, liquidity, bank capital, and asset quality, while the macroeconomic variables include GDP growth, inflation rate, and unemployment rate. The study employs a panel data regression method with a sample of 42 conventional banks listed on the Indonesia Stock Exchange from 2019 to 2023. The results reveal that liquidity and asset quality have a significant positive impact on credit risk, whereas bank capital, GDP growth, inflation rate, and unemployment rate have a significant negative impact on credit risk. Meanwhile, firm size, profitability, and the OEI ratio do not significantly influence credit risk. This research provides insights for financial managers in managing credit risk while considering macroeconomic conditions when making decisions. Additionally, for investors, the findings offer valuable perspectives on the factors to consider when evaluating banking institutions for investment purposes.